Influence of Physicochemical Properties of Lipopeptide Adjuvants on the Immune Response: A Rationale for Engineering a Potent Vaccine. Issue 39 (19th June 2018) - Eskandari, Sharareh; Pattinson, David J.; Stephenson, Rachel J.; Groves, Penny L.; Apte, Simon H.; Sedaghat, Bita; Chandurudu, Saranya; Doolan, Denise L.; Toth, Istvan
Abstract: Adjuvant development and understanding the physicochemical properties of particles and interpreting the subsequent immunological responses is a challenge faced by many researchers in the vaccine field. We synthesized and investigated the physicochemical properties and immunogenicity of a library of multiple epitope self‐adjuvant lipopeptides in a novel asymmetric arrangement. Vaccine candidates were synthesized using a combination of solid‐phase peptide synthesis and copper‐mediated click chemistry. In vivo studies showed that vaccine constructs containing a single OVA CD8 + T‐cell epitope and two N‐terminally located C16 lipid moieties were more effective at generating robust cellular immune responses compared to the same molecule containing multiple copies of the OVA CD8 + T‐cell epitope with or without the C16 moieties. Furthermore, attachment of the two C16 lipids to the N‐terminus provoked formation of long β‐sheet fibrils and was shown to induce a higher CD8 + donor T‐cell frequency and IFN‐γ secretion, compared to vaccine constructs with an internal lipid placement. A regression analysis indicated that particle secondary structure had a significant impact on CD8 + donor T‐cell frequency and cytolytic activity. In addition, IFN‐γ production was influenced significantly by particle shape. The findings of this research will impact the future design of a vaccine intended to elicit cellular immune responses. Abstract : Physicochemical characteristics correlate with immunological responses of OVA‐based lipopeptide self‐adjuvanting vaccine candidates. The vaccine candidate shown in the graphic contains a single OVA CD8 peptide epitope, two OVA CD4 peptide epitopes, and N‐terminally positioned C16 lipids that provoke formation of long fibrillar, β‐sheet particles. It also generated a robust cell‐mediated immune response and DC activation.